Electrochemical synthesis for new thiosemicarbazide complexes, spectroscopy, cyclic voltammetry, structural properties, and in silico study. (18th October 2020) - Refat, Moamen; El‐Metwaly, Nashwa; Yamany, Yamany B.; Althagafi, Ismail; Hameed, Ahmed; Alharbi, Arwa; Abualnaja, Matokah; Shah, Reem; Al‐Brakati, Ashraf; Al‐Humaidi, Jehan Y.
Abstract : A new thiosemicarbazide derivative ligand (HDCTS) was prepared from the reaction between 2, 4‐dinitrophenylhydrazine and 4‐chlorophenyl isothiocyanate. Co(II) and Cu(II) complexes were synthesized from HDCTS derivative by electrochemical method to reach preferable yield in a safe environment. The new complexes as well as the original ligand were fully characterized to establish their chemical formulae. The spectral (infrared, Raman, mass, and ultraviolet–visible), analytical (elemental, thermogravimetric analysis [TGA], and cyclic voltammetry), and conformational techniques were implemented for characterization. According to spectral data and magnetic moments, the octahedral arrangement was proposed around metals through mono‐negative bidentate mode of bonding. TGA discriminates and quantitatively evaluates the presence of water molecules within two complexes. Electrochemical study was interested for all new compounds and suggests the electrode couples to be close for quasi‐reversible behavior. Elaborated conformational study was displayed to extract significant characteristics, which assert firstly on the mode of bonding inside the complexes. The perfect distribution of NH and CS groups inside the optimized structures facilitates their coordination as spectrally proposed. Crystal explorer program was used to investigate the degree of contact between molecules inside crystal packing systems. Effective contribution in surface contact feature was noticed from O and Cl atoms. A certified in silico study concerning the docking feature of new compounds against effective proteins in allergy and inflammation diseases was done. According to data exported, a promising anti‐allergic or anti‐inflammatory efficiency is expected strongly from Cu(II)–DCTS complex. Abstract : Electrochemical synthesis and characterization for new Co(II) and Cu(II) complexes from new thiosemicarbazide derivative, were done. Detailed cyclic voltammetry study for new compounds was interested. Computational studies concerning surface properties, structural optimization, and in silico simulation towards allergy and inflammation were elaborately investigated.